Efektivitas Terapi Murottal Al- Quran Terhadap Kecemasan Pasien Pre Operasi - Asrul Asrul (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Presurgery is a potential or actual threat to a person's integrity that can elicit physiological and psychological stress reactions, including emotional reactions in the form of fear during the preoperative period. Objective: Knowing the effectiveness of Al-Qur'an murottal therapy on the anxiety level of preoperative patients. Method: Qualitative research with the descriptive design of case studies. The methods used are interviews and observations. Use of the Hamilton Anxiety Rating Scale questionnaire. Result: Showed a significant decrease in anxiety levels after being given Al-Qur'an murottal therapy for 10 minutes and showed an effect resulting from listening to the Al-Qur'an Murottal. The changes shown were relaxation or decreased nerve tone, resulting in the relaxation of arteries and increased blood levels on the skin, accompanied by a decrease in heart rate. Conclusion: That quranic murottal therapy may lower anxiety in preoperative patients. Listening to the murottal reading of the Al-Qur'an through audio is one alternative that can be a calmer and self-reminder